Apply Yourself: Racial and Ethnic Differences in College Application - Sandra E. Black; Kalena E. Cortes; Jane Arnold Lincove (Institute for the Study of Labor (IZA), 2015)
Access to higher education begins with a student's decision whether and where to apply to college. This paper examines racial and ethnic differences in college application behavior of high school graduates, using two recent graduation cohorts from Texas. We estimate racial and ethnic differences in the probability of applying to college, controlling for a student's college readiness, high school quality, certainty of college admissions, and high school fixed effects. We then investigate racial and ethnic differences in the choice of where to apply. We enhance the typical model of college matching by considering the social setting and high school feeder patterns of state universities. We find that racial and ethnic gaps in application rates, particularly for Hispanic students, are not explained by differential levels of college readiness, high school quality, or information regarding college admission processes. When applying to college, minorities are influenced by more than just matching their academic ability to the institution, and prefer institutions with a large proportion of same race students and campuses where same race students from their high school have been successful in the past.
Keywords: I21; I23; I24; J15; J18; 330; college application; college readiness; high school quality; undermatching; race and ethnicity; low-income students; Texas Top 10% Plan; automatic admissions